Analisis Faktor-Faktor Yang Mempengaruhi Transfer Pricing Pada Perusahaan Sektor Industri Di Indonesia - Mohammad Ridwan; Annisa Diah Arofah; Anindya P.R.Z Putri; Untung Prasetyo Ilham (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
This research is aimed at empirically proving whether Transfer pricing is affected by the variables Tax, Exchange Rate, Company Size, Bonus Mechanisms, Profitability, and Leverage in industrial sector companies listed on the Indonesia Stock Exchange in 2018-2021. This sampling uses the Purposive Sampling method from 30 companies for samples from industrial sector companies listed on the Indonesia Stock Exchange in 2018-2021. The documentation was conducting data collection techniques with the company's annual report through each company's website. The research uses multiple linear regression analysis techniques with research data processing tests using SPSS version 26. This study shows that the simultaneous model of Transfer pricing is influenced by the variables Tax, Exchange Rate, Firm Size, Bonus Mechanism, Profitability, and Leverage. The partial test results show that Transfer pricing is influenced by Tax, Firm Size, Bonus Mechanism, Profitability, and Leverage variables which affect Transfer pricing. The Exchange Rate does not affect transfer pricing